2013
DOI: 10.1186/1479-5876-11-262
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the percentage of surface receptors and cytotoxic granules positive natural killer cells in patients with pancreatic cancer, gastric cancer, and colorectal cancer

Abstract: BackgroundDigestive malignancies, especially pancreatic cancer (PC), gastric cancer (GC), and colorectal cancer (CRC), still occur at persistently high rates, and disease progression in these cancers has been associated with tumor immunosurveillance escape. Natural killer (NK) cell dysfunction may be responsible for this phenomenon, however, the exact relationship between tumor immunosurveillance escape in digestive malignancies and NK cell dysfunction remains unclear.MethodsPercentage of the surface receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 39 publications
8
113
0
1
Order By: Relevance
“…However, this increase was not associated with tumor progression. 27 It was shown that an increased level of CD158b was observed in involved lymph nodes compared to uninvolved lymph nodes of melanoma patients. 35 In addition, CD200, the ligand of the inhibitory receptor CD200R, has been found to be over-expressed in multiple hematological malignancies, such as B-cell chronic lymphocytic leukemia, multiple myeloma and acute myeloid leukemia.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this increase was not associated with tumor progression. 27 It was shown that an increased level of CD158b was observed in involved lymph nodes compared to uninvolved lymph nodes of melanoma patients. 35 In addition, CD200, the ligand of the inhibitory receptor CD200R, has been found to be over-expressed in multiple hematological malignancies, such as B-cell chronic lymphocytic leukemia, multiple myeloma and acute myeloid leukemia.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…Decreased expression of NKG2D has been observed in most cancer patients, which include breast cancer (BC), lung cancer (LC), colorectal cancer (CRC), cervical cancer (CC), pancreatic cancer (PC), gastric cancer (GC) and HCC. [26][27][28][29][30][31] With disease progression, decreased expression of NKG2D can be correlated with decreased NK cell function, most notably reduced cytotoxicity. The significantly 22,28,[34][35][36] Moreover, these alterations are not limited to activating receptors on NK cells.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…The importance of NKcell receptors in mediating antitumor immune response is further supported by the identification of several mechanisms of immune escape, mainly consisting in the downregulation of activating receptors and their ligands, or alternatively in the upregulation of inhibitory receptor-ligand pairs. [9][10][11][12] Additional mechanisms of immune evasion have also been described, such as escape from NKG2D-mediated immunosurveillance through shedding of NKG2D ligand MICA. 13 Few data are available about the role played by NK receptor expression and signaling in the determination of HCC outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Higher expression of certain inhibitory KIR receptors has been shown in pancreatic, gastric, and CRC without association with disease progression [15]. Other studies in patients with metastatic melanoma, as well as in NSCLC and breast cancer, show an increase in the expression of CD158a and CD158b inhibitory KIR receptors on NK cells [33,[49][50][51] that in melanoma negatively correlates with NK cell cytotoxicity [33].…”
Section: Killer Cell Immunoglobulin-like Receptor Familymentioning
confidence: 97%
“…Decreased expression of some NCR has been reported in several malignancies, namely low NKp46 in melanoma, pancreatic, gastric, cervical cancer, and acute myeloid leukemia (AML) [15][16][17], NKp44 in numerous solid and hematological malignancies, and NKp30 in breast, hepatocellular cancer (HCC), chronic lymphocytic leukemia (CLL), and AML [15,16,[18][19][20]. Moreover, ILC3 cells expressing NKp44 activating receptor in human nonsmall-cell lung cancer (NSCLC) tissue were shown to have tumor protective role [4].…”
Section: Natural Cytotoxic Receptorsmentioning
confidence: 99%